Family Education in Exclusive Breastfeeding: Husband's Knowledge and Attitude in Supporting Breastfeeding Women - Wiwin Widayani; Dezh Jihaan Miftah; Achmad Hufad; Viena Rusmiati Hasanah; Uyu Wahyudin; Asep Saepudin; Faridah Hanim Yahya (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2025)
Objective: In Indonesia, breastfeeding rates are relatively low, even though the benefits of exclusive breastfeeding are widely acknowledged. In 2022, just 67.96% of Indonesians were exclusively nursing, according to a WHO assessment. One of the numerous causes of this low number is the husband's lack of support. For exclusive breastfeeding to be successful, the husband's support is essential. When a spouse accepts and supports his wife's decision to exclusively breastfeed, it might be beneficial for nursing mothers. This study aimed to determine the relationship between the attitudes and knowledge of husbands on exclusive breastfeeding. Method: This study sought to ascertain how husbands' attitudes and knowledge about exclusive breastfeeding related to each other. This cross-sectional survey design, a quantitative correlational study, employed 106 samples. The data was analyzed using the chi-square test, and the results indicated a significant (p <0.05) relationship between the husband's skill and exclusive breastfeeding. One hundred six samples were used in this cross-sectional survey design, which was a quantitative correlational investigation. Results: The chi-square test was performed to analyze the data, and the findings showed a significant correlation (p <0.05) between exclusive breastfeeding and the husband's expertise. Up to 95.7% of respondents knew much about exclusive breastfeeding, compared to 47.5% who did not. The analysis indicated a substantial (p <0.05) correlation between exclusive breastfeeding and the husband's attitude. Novelty: This research is unique in that it focuses on spouses or couples.